Processamento e caracterização de cerâmicas eletro-ópticas do sistema ferroelétrico (Pb1-xLax)TiO3 - Londoño Badillo, Fernando Andrés (2006)
The ferroelectric titanate of lead modified with Lanthanum metal system (or PLT) is the most studied of the perovskite structure. It is known that ceramic bodies with specify compositions and adequately chemical preparations can present transparency. However, a quantitative or qualitative analysis of its electro-optics characteristics was not carried through. Therefore, in this work it was ceramic preparation of PLT and the characterization and analysis of concentration of Lanthanum metal and the conditions of processing influence in its microstructural, dielectric, ferroelectrics, optic, structural and electro-optics properties. In this work the solid state was used in the obtained of PLT, using the nominal formula (Pb1-xLax)TiO3, with 0.18_ x _ 0.23. Ceramic bodies had been firing by the uniaxial Hot Pressing technique. Heat treatments in conventional oven under O2 and PbO atmosphere, had been used for the improvement of the transmitance of the samples. In the DRX analysis it was observed formation of perovskite phase with tetragonal symmetry as principal in the powder with little variation of the tetragonalidade factor in function of the Lanthanum metal concentration. For the densitied ceramics, it was meet perovskite phase with tetragonal symmetry and an reduction of the tetragonalidade factor of with the increase of the Lanthanum metal concentration. The grain average size of the ceramic bodies linearly increased with the Lanthanum metal concentration, presenting distinct dependence for each composition in relation to the heat treatment. The dielectric and ferroelectrics properties had been affected by the high conductivity presented for the ceramic bodies with less than 20h of thermal treatment. Such conductivity, as well as the opacity and the yellow color observed in the samples, was associated with the presence of the phase PbO in the grain boundaries. However, high values of transmitance in the next infra-red and visible region and less dielectric losses in low frequencies could have been observed in samples with 20h thermal treatment, depending on the Lanthanum metal concentration. For x=0.23, the highest concentration of analyzed La, the ceramic bodies thermal treatments presented a reduction in the transmittance, probably due ix to the effect of light scattering of rich Lanthanum metal phases precipitated in the grain boundaries (even though it was not detected for DRX). For the first time, the electro-optic coefficients could have been considered for PLT ceramics. The results had shown the importance of thermal treatment after-hot pressing and the concentration of Lanthanum metal in the obtaining of the transparent ceramic bodies with structural, microstructural, electric and optic properties adjusted for the technological applications.